Sexualidade e campesinidade: percepções e vivências de jovens em escola do campo no sudoeste do Paraná - Belusso, Andréia (2019)
This research sought to present some reflections about the dimension of sexuality in rural space, outlining concerns about what are the knowledge and practices that the young students of a school in the Southwest of Paraná construct/deconstruct and activate to live their sexuality. The specialized literature does not focus on the perceptions and experiences of sexuality in contexts linked to activities in the field or in non-urban areas. The research locus was a state high school located in Southwest Paraná. According to a qualitative approach, the data collection process employed Focus Group interviews whose data interpretation applied the content analysis technique. The young women and girls who participated in this study revealed significant aspects that marked the intense process of the constitution of their sexualities in the environment in which they live. We seek to reflect on how the meanings of gender are present in work, in homes, in things, in institutions, in values, in social relations in this way, by extrapolating the level of sexual actions. Young people from rural Southwest still constitute their identities from the existence of an asymmetric pattern in gender relations. The inequality that still naturalizes the double working day of women between the home and the farm. Inequalities that naturalize restrictions on the free movement of women in some social spaces. Another issue that emerged in our investigation was the influence of socializing institutions such as the family, school, and church on the practices and conceptions and the construction of the sexuality of these young people. As the main corpus of the research, we describe how this rural is composed of bodies composed of desires, affections, sexual experiences and bodies that escape the heteronormative norm.